Combined hydroxyurea and ETA receptor blockade reduces renal injury in the humanized sickle cell mouse. (20th September 2018) - Taylor, Crystal; Kasztan, Malgorzata; Tao, Binli; Pollock, Jennifer S.; Pollock, David M.
Abstract: Aim: The objective of this study is to determine if ambrisentan (ETA selective antagonist) and hydroxyurea (HU) treatment has a synergistic effect on renal injury in sickle cell nephropathy when compared to HU treatment alone. The premise of the study is based on recent studies showing that endothelin‐1 (ET‐1) contributes to the pathophysiology of nephropathy in sickle cell disease (SCD) and that ETA receptor blockade improves renal function and protects against renal injury. Hydroxyurea (HU) is commonly prescribed for the treatment of SCD and has been shown to reduce renal injury in patients with SCD. Methods: Male 12‐week‐old humanized sickle mice (HbSS) and their genetic controls (HbAA) were treated with vehicle, HU, ambrisentan, or HU with ambrisentan for 2 weeks and renal structure and function were assessed. Results: Vehicle treated HbSS mice exhibited significant proteinuria compared to vehicle treated HbAA mice. HbSS mice also displayed significantly elevated plasma ET‐1 concentrations and decreased urine osmolality compared to HbAA controls. Proteinuria was significantly lower in both HU and ambrisentan treated animals compared to vehicle treated HbSS mice; however, there was no additional improvement in HbSS mice treated with combined ambrisentan and HU. The combination of HU and ambrisentan resulted in significantly lower KIM‐1 excretion, glomerular injury, and interstitial inflammation than HU alone. Conclusion: These findings indicate that HU and ETA receptor blockade produce similar reductions in renal injury in the humanized sickle mouse suggesting that both treatments may converge on the same mechanistic pathway.